2021
DOI: 10.1123/wspaj.2020-0056
|View full text |Cite
|
Sign up to set email alerts
|

Women Rugby Union Coaches’ Experiences of Formal Coach Education in Ireland and the United Kingdom: A Qualitative Study

Abstract: Although the sport of rugby union has expanded globally in both the men’s and women’s formats recently, there remains an under-representation of women coaches across all contexts. Research has focused its analysis on the under-representation of women coaches in a select few sports such as soccer. No extant research has empirically analyzed this under-representation within rugby union. This study addressed this research lacuna on why this under-representation exists from the perspective of 21 women rugby union … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 45 publications
(56 reference statements)
1
8
0
1
Order By: Relevance
“…72,113,118,122,132 Only two studies specifically investigated coaches working in women's rugby (n = 2, 2%). 31,48 Thirty-three percent (n = 35, 33%) of studies were on youth rugby only, 52% (n = 55, 52%) on senior rugby, nine percent (n = 9, 9%) on both youth and senior rugby and the remaining percentage of the studies did not specify. Only 23 studies (n = 23, 22%) reported all demographic data.…”
Section: Numerical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…72,113,118,122,132 Only two studies specifically investigated coaches working in women's rugby (n = 2, 2%). 31,48 Thirty-three percent (n = 35, 33%) of studies were on youth rugby only, 52% (n = 55, 52%) on senior rugby, nine percent (n = 9, 9%) on both youth and senior rugby and the remaining percentage of the studies did not specify. Only 23 studies (n = 23, 22%) reported all demographic data.…”
Section: Numerical Analysismentioning
confidence: 99%
“…Forty-three studies reported on coaches' training knowledge. 18,29,31,36,37,40,[42][43][44][48][49][50][51][52][53][54][55][56][57][58][61][62][63][64][66][67][68][69][70]73,74,76,80,81,[85][86][87]89,90,92,93,128,131 Eight of these studies were based on rugby league. 43,56,62,64,[66][67][68]81 Coaches agreed that monitoring players are important for training.…”
Section: Thematic Analysismentioning
confidence: 99%
“…The two primary delivery methods of formal CE are through higher education (HE) or through National Governing Bodies, federations, or other sport-specific organizations. There are numerous studies on sport-specific CE, such as recent examples examining women coaching Australian Rules Football (Carson et al, 2021) and women coaching rugby (Barrett et al, 2021). However, Trudel and colleagues (2020) noted a lack of studies on CE in higher education.…”
Section: The Best Of Both Worlds? a Joint Reflection On One Higher Education Coach Education Programmentioning
confidence: 99%
“…Theorisation of how socio-cultural issues affect women's developmental coach pathways (Sisjord et al 2020), their experiences on formal coach education courses (Barrett, Sherwin and Blackett 2021) and the formation of their gendered identities (Mennesson 2012) has been increasingly made through the work of Pierre Bourdieu. Indeed, Bourdieu's theorisation of the practices social agents employ and embody was based on their socialisation and immersion to the cultural surroundings; "one must remember that, ultimately, objective relations do not exist and do not really realize themselves except in and through the system of dispositions of the agents, produced by the internalization of objective conditions" (Bourdieu and Zanotti-Karp, 1968: 705).…”
Section: Theoretical Frameworkmentioning
confidence: 99%